2011
DOI: 10.1097/hjh.0b013e32834069bd
|View full text |Cite
|
Sign up to set email alerts
|

Effects of verapamil added-on trandolapril therapy in hypertensive type 2 diabetes patients with microalbuminuria: the BENEDICT-B randomized trial

Abstract: In hypertensive type 2 diabetes patients with microalbuminuria, verapamil added-on trandolapril did not improve renal or cardiovascular outcomes. Independent of verapamil, trandolapril normalized albuminuria in half of patients and this translated into significant cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 21 publications
1
39
0
6
Order By: Relevance
“…The novel finding here was that, in patients with regression of microalbuminuria, the rate of fatal and nonfatal cardiovascular events was reduced by almost 50% (from 18.9% to 9.8%) compared with those without regression. 64 The BENEDICT trial found that 3.6 year treatment with the ACE inhibitor, trandolapril, compared with non-ACE inhibitor therapy reduced the risk of progression to microalbuminuria from 10.9% to 5.8% in 1204 type 2 diabetes patients with normal urinary albumin excretion at inclusion, an effect that was observed at comparable BP control between treatment arms. 65 A virtually identical study, the ROADMAP study, repeated 7 years later with an ARB instead of an ACE inhibitor in a similar typology of patients showed that 3.2 years of olmesartan therapy reduced the incidence of microalbuminuria compared with placebo from 9.8% to 8.2%, an effect that was observed in parallel with better BP control on olmesartan and that was not significant any longer when analyses were adjusted for BP levels in the two treatment arms.…”
Section: Ace Inhibitors Arbs or Both?mentioning
confidence: 99%
“…The novel finding here was that, in patients with regression of microalbuminuria, the rate of fatal and nonfatal cardiovascular events was reduced by almost 50% (from 18.9% to 9.8%) compared with those without regression. 64 The BENEDICT trial found that 3.6 year treatment with the ACE inhibitor, trandolapril, compared with non-ACE inhibitor therapy reduced the risk of progression to microalbuminuria from 10.9% to 5.8% in 1204 type 2 diabetes patients with normal urinary albumin excretion at inclusion, an effect that was observed at comparable BP control between treatment arms. 65 A virtually identical study, the ROADMAP study, repeated 7 years later with an ARB instead of an ACE inhibitor in a similar typology of patients showed that 3.2 years of olmesartan therapy reduced the incidence of microalbuminuria compared with placebo from 9.8% to 8.2%, an effect that was observed in parallel with better BP control on olmesartan and that was not significant any longer when analyses were adjusted for BP levels in the two treatment arms.…”
Section: Ace Inhibitors Arbs or Both?mentioning
confidence: 99%
“…The BENEDICT-B trial showed that addition of verapamil did not improve albuminuria in T2DM patients with nephropathy. Conversely, the trandolapril treatment caused a reduction of albuminuria in 50% of the patients, and this reduction translated to a significantly lower rate of cardiovascular complications in these patients 17 . These results are in sharp contrast to the DIABHYCAR study, which failed to show the beneficial effect of ACEI ramipril on cardiovascular and renal outcomes in T2DM patients with established albuminuria 18 .…”
Section: Acei and Arb In Type 2 Diabetes Mellitus And Nephropathymentioning
confidence: 96%
“…Since the development of albuminuria is a major risk factor for the cardiovascular complications and death in this patient population, the authors concluded that in T2DM hypertensive patients with preserved renal function, ACEIs may be the treatment of choice 16 . In the subsequent BENEDICT-B trial they examined the effects of the addition of verapamil on trandolapril therapy in hypertensive T2DM petients with established microalbuminuria 17 . The BENEDICT-B trial showed that addition of verapamil did not improve albuminuria in T2DM patients with nephropathy.…”
Section: Acei and Arb In Type 2 Diabetes Mellitus And Nephropathymentioning
confidence: 99%
“…[542]. Такой же вывод был сделан в исследовании выживае-мости при назначении кандесартана цилексетила в остром периоде инсульта (ACCESS) [543], которое свидетельствовало о положительном эффекте приме-нения кандесартана в течение 7 дней после острого при диабетической, так и при недиабетической нефро-патии и у больных с сердечно-сосудистыми заболевани-ями [513,537], а также эффективно предотвращает первое появление микроальбуминурии [329,538]. Ни одно из этих исследований не обладало достаточной статистической мощностью для оценки влияния на сер-дечно-сосудистые конечные точки.…”
Section: цереброваскулярная болезнь 6101 острый инсультunclassified